Produktifitas Tenaga Kerja Berdasarkan Faktor Demografi di Perusahaan Manufaktur - Gandhi Pawitan; Erwinda (Business Administration Department - Universitas Katolik Parahyangan, 2013)
Labor productivity is one measure of corporate performance. In this article, the levelof labor productivity is calculated based on the normal time per worker in completingthe work. The level of labor productivity can be affected by demographic factors,such as gender and age. This study aims to analyze the relationship between laborproductivity with demographic factors. This research was conducted at the companyconvection in the Bandung city. The research was done by observing the level oflabor productivity of 12 people, for 3 days, with 6 observations per day. The resultsof the calculation of the index of labor productivity on average by 149.18%, which isabove the average. Productivity index does not have a difference between male andfemale worker. While the variable age has a negative relationship with productivity,but statistically is not significance.Keywords: Labor productivity, demographic factors, productivity measurement.